(untitled) (Revista Ciência Agronômica, 2017)
The cultivation of irrigated rice is subject to the occurrence of various diseases, where damage causes losses in productivity. Alternatives are currently being sought to control these diseases, with biocontrol a viable possibility. With the aim of broadening the spectrum of action of biocontrol, this study evaluated the effect of combinations of biocontrol bacteria on rice blast (Pyricularia grisea), brown spot (Bipolaris oryzae) and leaf scald (Gerlachia oryzae) in rice plants. The effect of isolate combinations was assessed by microbiolization of seeds from the rice cultivar El Paso L144 with suspensions of the bacteria DFs185 (Pseudomonas synxantha), DFs223 (P. fluorescens), DFs306 (unidentified), DFs416 and DFs418 (Bacillus sp.), used individually or in a combination of two, three or four compatible isolates. Seeds treated with Carboxin Thiram fungicide (T+F) at a final dosage corresponding to 3 ml kg-1 were used as control. Considering the leaf diseases together, eight treatments significantly controlled all three diseases, and were superior to the treatment with fungicide. Among these treatments, seven were combinations. Only the DFs306 bacteria were able to control the three diseases when used individually. It can therefore be presumed that combinations of bacteria, when microbiolized in rice seeds, can broaden the spectrum of action for the control of rice blast, brown spot and leaf scald.